2014
DOI: 10.1177/2047487314537916
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for, and prevalence of, sleep apnoea in cardiac rehabilitation facilities in Germany: The Reha-Sleep registry

Abstract: The findings of this study indicate that more than one-third of patients undergoing cardiac rehabilitation in Germany have sleep apnoea, with one-third having moderate-to-severe SDB that requires further evaluation or intervention. Inclusion of sleep apnoea screening as part of cardiac rehabilitation appears to be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Our analyses indicated that the presence of a sleep disturbance at 4 months, however, could have a potential detrimental effect on cardiac rehabilitation efforts via reduction of treatment adherence, lower self-efficacy, and increased depression and anxiety. It is already known that cardiac patients with sleep disturbances have daytime sleepiness, fatigue and, as a result, reduced physical activity and find it more difficult to lose weight than those without a sleep disorder (Skobel et al, 2014). Our analysis which controlled for age, sex and type of cardiac patient (CABGS, AMI or PCI) suggests that these pathways resulting from earlier sleep disturbance may potentially result in lower patient self-efficacy and increased risk of further heart problems at 12 months following the initial cardiac event.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses indicated that the presence of a sleep disturbance at 4 months, however, could have a potential detrimental effect on cardiac rehabilitation efforts via reduction of treatment adherence, lower self-efficacy, and increased depression and anxiety. It is already known that cardiac patients with sleep disturbances have daytime sleepiness, fatigue and, as a result, reduced physical activity and find it more difficult to lose weight than those without a sleep disorder (Skobel et al, 2014). Our analysis which controlled for age, sex and type of cardiac patient (CABGS, AMI or PCI) suggests that these pathways resulting from earlier sleep disturbance may potentially result in lower patient self-efficacy and increased risk of further heart problems at 12 months following the initial cardiac event.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Recently published data from the Reha-Sleep registry, investigating the prevalence of SDB in cardiac rehabilitation patients, reported that clinically significant SA (AHI ≥15/h) was documented in 33% of patients. 19 Applying a cut-off level of an AHI of 15, the SA prevalence in our study was 14% (16.4% in men, 6.5% in women). Our study, using a cross-sectional design, is fraught with problems of uncertainty, bias and confounding.…”
Section: Discussionmentioning
confidence: 56%
“…In 3 other studies, the proportion of patients enrolled in CRPs with a previous diagnosis of OSA was 1.8% (n = 22/1293), 26 3.9% (n = 15/383), 25 and 17% (n = 20/118). Education and communication with the patient and physician resulted in 3 of the 7 patients (42.9%) who responded to the 6-month questionnaire and had a conversation with their physician resuming CPAP treatment.…”
Section: Discussionmentioning
confidence: 87%